The Influence of Discipline, Conflict and Job Stress on Employee Job Satisfaction at PT. Transco Pratama CRF Sungai Betung Dharmasraya - Rahmatullah Pratama (Kirana Publisher (KNPub), 2023)
This research aims to determine the influence of discipline, conflict and work stress on employee job satisfaction at PT. Transco Pratama CRF Sungai Betung Dharmasraya. The method used is a quantitative method based on a population and sample of 70 employees. The data collection methods used were surveys and questionnaires. The analytical method used is correlation analysis and multiple linear regression analysis analisis using SPSS version 23.0. From the results of the analysis carried out, it shows that there is a positive and significant influence between partial discipline on employee job satisfaction with a significant value of 0.048<0.050 and a calculated value of 2.013, there is a positive and significant influence between partial Conflict on Employee Job Satisfaction with a significant value of 0.000<0.050 and a calculated value of 4.492, there is a positive and significant influence between partial Job Stress on Employee Job Satisfaction with a significant value of 0.007<0.050 and a calculated value of 2.798 and there is a simultaneous influence of Discipline, Conflict and Work Stress on Employee Job Satisfaction of 0.725 or 72.5%